PENENTUAN RUTE TRANSPORTASI TERPENDEK UNTUK MEMINIMALKAN BIAYA MENGGUNAKAN METODE SAVING MATRIKS - Ikfan, Noer; Masudin, Ilyas (Jurnal Ilmiah Teknik Industri, 2013)
This paper presents a case study of vehicle routing problem at CV. Boang Shutlecocok which is engaged in the distribution of Shutlecock. To fulfill market demand, The company operates to transmit Shutlecock to every distributors throughout the eastern Java. Because of Shutlecock distribution is from warehouse to distributors and every distribution are quite far from the warehouse, so that causing the distribution cost incurred by CV. Boang Shuttlecock increased. In this study a method to implement VRP (Vehicle Routing Problem) based on saving matrix, in which the method will provide the shortest route to minimize costs, distance and minimizing distribution time spent by the company. Before the implementation of saving matrix method on the company, total distribution costs incurred by the company amounted to Rp.5,882,771/period, after the VRP method applied, obtained a total cost of Rp.5,239,003/period, in order to obtain the distribution cost savings per period of Rp.643,764 or approximately 10.94%.